Congenital Heart Disease as a Warning Sign for the Diagnosis of the 22q11.2 Deletion - Grassi,Marcília S. (2014)
Background: To alert for the diagnosis of the 22q11.2 deletion syndrome (22q11.2DS) in patients with congenital heart disease (CHD). Objective: To describe the main CHDs, as well as phenotypic, metabolic and immunological findings in a series of 60 patients diagnosed with 22q11.2DS. Methods: The study included 60 patients with 22q11.2DS evaluated between 2007 and 2013 (M:F=1.3, age range 14 days to 20 years and 3 months) at a pediatric reference center for primary immunodeficiencies. The diagnosis was established by detection of the 22q11.2 microdeletion using FISH (n = 18) and/or MLPA (n = 42), in association with clinical and laboratory information. Associated CHDs, progression of phenotypic facial features, hypocalcemia and immunological changes were analyzed. Results: CHDs were detected in 77% of the patients and the most frequent type was tetralogy of Fallot (38.3%). Surgical correction of CHD was performed in 34 patients. Craniofacial dysmorphisms were detected in 41 patients: elongated face (60%) and/or elongated nose (53.3%), narrow palpebral fissure (50%), dysplastic, overfolded ears (48.3%), thin lips (41.6%), elongated fingers (38.3%) and short stature (36.6%). Hypocalcemia was detected in 64.2% and decreased parathyroid hormone (PTH) level in 25.9%. Decrease in total lymphocytes, CD4 and CD8 counts were present in 40%, 53.3% and 33.3%, respectively. Hypogammaglobulinemia was detected in one patient and decreased concentrations of immunoglobulin M (IgM) in two other patients. Conclusion: Suspicion for 22q11.2DS should be raised in all patients with CHD associated with hypocalcemia and/or facial dysmorphisms, considering that many of these changes may evolve with age. The 22q11.2 microdeletion should be confirmed by molecular testing in all patients.